Meta-Analysis of Salmon Trophic Ecology Reveals Spatial and Interspecies Dynamics Across the North Pacific Ocean - Graham, Caroline; Pakhomov, Evgeny A.; Hunt, Brian P. V. (Frontiers in Marine Science, 2021)
We examined spatial patterns in diet, trophic niche width and niche overlap for chum, pink and sockeye salmon across the North Pacific during 1959–1969. This is a baseline period before major hatchery enhancement occurred coinciding with a negative phase of the Pacific Decadal Oscillation. Large-scale (between regions) and fine-scale (within regions) spatial and interspecies differences were apparent. In the Western Subarctic, all species tended to consume zooplankton. In the Bering Sea, chum consumed zooplankton, while sockeye and pink alternated between zooplankton and micronekton. In the Gulf of Alaska / Eastern Subarctic, chum and sockeye specialized on gelatinous zooplankton and cephalopod prey, respectively, while pink consumed a mixture of zooplankton and micronekton. The highest diet overlap across the North Pacific was between pink and sockeye (46.6%), followed by chum and pink (31.8%), and chum and sockeye (30.9%). Greater diet specialization was evident in the Gulf of Alaska / Eastern Subarctic compared to the Western Pacific. Generally, species had higher niche width and overlap in areas of high prey availability, and this was particularly evident for chum salmon. In addition to the large-scale trophic patterns, our data revealed novel fine-scale spatial patterns, including latitudinal, onshore-offshore, and cross-gyre gradients. Our results showed that pink tended to be more generalist consumers, and their diets may be a better reflection of overall prey presence and abundance in the environment. Conversely, chum and sockeye tended to be more specialist consumers, and their diets may provide a better reflection of interspecies dynamics or prey availability. This study provides a baseline for comparison with current and future changes in salmon marine ecology and North Pacific ecosystems. Finally, we identify two important data gaps that need addressing, that of improved taxonomic resolution diet data for Pacific salmon and focused research on sub-mesoscale oceanographic features that may play an important role in salmon health and productivity.